Comprensión lectora y su incidencia en el rendimiento académico de los estudiantes de la escuela de educación básica “24 de Mayo” de la parroquia San Juan cantón puebloviejo provincia los Ríos - Vera Bajaña, Carmen Magaly (2015)
This paper grade: reading comprehension and its impact on the academic performance of students of the school of basic education "May 24" of the parish San Juan Pueblo Viejo Canton Province Rivers. Reading comprehension being an impediment to the teaching of reading as this limits them to students to conduct an analysis and interpretation of what he reads. This work has as main objective to identify the methods or techniques that teachers have applied for reducing problems of reading comprehension in students of third and sixth year of basic consideration as concerning students, teachers, parents. Learning deficiency in reading comprehension implies that the student will not only have problems in the classroom but in their social status, which is why teachers have to be aware of how to assess student achievement as this affects one way different in each of these students Applying techniques to develop a love of reading in order to improve the process of reading comprehension in students who have this difficulty helping to improve their teaching and learning Known to us a true picture to try to achieve this degree work get items, real trial that will pattern and alternative solutions to the problem raised.